Characterization of thrombophilia-related plasmas evaluated by anticoagulants-mediated thrombin and plasmin generation assays. Issue 6 (September 2022) - Hashimoto, Naoki; Ogiwara, Kenichi; Matsumoto, Tomoko; Furukawa, Shoko; Takeyama, Masahiro; Nogami, Keiji
Abstract : Disturbances in the balance between coagulation, anticoagulation and fibrinolysis may lead to thrombosis or haemorrhage. Simultaneous assessments of thrombin and plasmin facilitate overall understandings of pathological haemostasis, especially for thrombophilia. Here, we characterized coagulation–fibrinolysis potentials in plasmas with thrombophilia using anticoagulants-mediated thrombin-plasmin generation assay (T/P-GA). T/P-GA was initiated by adding tissue factor, tissue-type plasminogen activator and anticoagulants [recombinant-thrombomodulin (rTM), activated protein (P)C (APC) and antithrombin (AT)], followed by simultaneous thrombin generation and plasma generation monitoring. Patients' plasmas with PC-deficiency (PC-def), PS-deficiency (PS-def), AT-deficiency (AT-def), factor VLeiden (FVL) and antiphospholipid syndrome (APS) were evaluated. A ratio of peak-thrombin (or peak-plasmin) with and without anticoagulants was calculated as anticoagulants (+)/anticoagulants (−). First, TG, in rTM-mediated, PC-def, PS-def and FVL showed higher peak-thrombin ratios than the controls, whereas AT-def and APS exhibited no differences from the controls. In APC-mediated, PC-def, PS-def and AT-def showed low peak-thrombin ratios, similar to the controls, but immune-depleted PS-def (<1%) showed the higher ratio than the controls. FVL and APS showed higher peak-thrombin ratios than the controls. In AT-mediated, peak-thrombin ratios in PS-def, PC-def and APS were lower than in controls, but those in AT-def and FVL was not significantly different from the controls. Second, PG, in rTM-mediated, all thrombophilia plasmas showed low peak-plasmin ratios (∼0.5), but no significant difference was observed, relative to the controls. In APC and AT-mediated, peak-plasmin ratios in thrombophilia-related plasmas were similar to the controls (∼1.0). Anticoagulants-mediated T/P-GA may classify thrombin generation characteristics in thrombophilia-related plasmas upon adding anticoagulants.